2022
DOI: 10.3389/fpsyg.2022.961960
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of perceptual anticipation in combat sports between experts and non-experts: A systematic review and meta-analysis

Abstract: In order to systematically evaluate perceptual anticipation between experts and non-experts for different kinds of combat sports, we needed to perform a comprehensive assessment. In this systematic review and meta-analysis, we searched four English-language and three Chinese-language databases that used expert/non-expert research paradigms, to explore perceptual anticipation in combat sports. We employed a random effects model for pooled analyses using the inverse variance method. We included 27 eligible studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
(52 reference statements)
0
1
0
1
Order By: Relevance
“…Importantly, the formation of these space–time mapping relationships by message senders was not predetermined with message receivers but emerged spontaneously within group dynamics ( Grasso et al, 2022 ). This finding underscored the substantial influence of previous sensorimotor experiences on group behavior ( Zhang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 72%
“…Importantly, the formation of these space–time mapping relationships by message senders was not predetermined with message receivers but emerged spontaneously within group dynamics ( Grasso et al, 2022 ). This finding underscored the substantial influence of previous sensorimotor experiences on group behavior ( Zhang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 72%
“…Examining the specific locations participants were looking at in each condition would have provided a more detailed comparison. Previous research has demonstrated that experts in boxing ( Martínez de Quel and Bennett, 2019 ) and combat sports ( Zhang et al, 2022 ) utilize specific areas of interest during visual exploration. Experts tend to distribute their gaze more towards areas such as the head and trunk of the opponent, while novices tend to focus more on the forehand and pelvis regions.…”
Section: Discussionmentioning
confidence: 99%
“…Проте дослідження та розробка методології використання засобів тренування боксерів на основі ритмічності як однієї з характеристик рухової діяльності мають фрагментарний характер Визначено, що отримані дані не мають суттєвих протиріч з наявними в нещодавніх дослідженнях . Проте, зафіксовані показники дещо відрізняються щодо виявлених у літературі Zhang, et al, 2022) Дослідники не мають протиріч щодо важливості підвищення швидкості рухів боксерів як запоруки технічного вдосконалення (Bingul, et al, 2018;Chen, et al, 2021). Навіть виділяючи окрему типологічні групу бійців, що досягають високої результативності двобою за рахунок швидкісних здібностей (Aksutin, & Korobeynikov, 2014).…”
Section: ефективність використання ритмічної стимуляції для вдосконал...unclassified